Effectiveness of National Language Policy of Nepal (Orchid Academia Siraha, 2024)
The present study considers the policy and position of languages recognized by the nation to different languages spoken in Nepal. The study aims to see the effectiveness of national language policy on the preservation of education and language. This qualitative study adopts constitution, census of population, reports on language commissions as primary sources of data and research articles and books as secondary sources of data. Based on the constitution of Nepal 2047 and population census 2048, the language commission of 2050 took the basis to classify on the basis of geographical area, native speakers, multilingual status, languages of indigenous communities and mother tongues are seen relevant. Learning achievement is found to be well because of mother tongue policy. The implementation of mother-tongue based education in basic level proposed by language commission 2050, has played the supportive role for learning achievement of the students. It is also recommended that the provisions documented regarding language use by interim constitution of Nepal 2063, and the constitution of Nepal 2072 must be made practical and implemented accordingly. If implemented properly, it will facilitate the basic level students and learning will be effective.